Integrasi Media Digital dalam Pembelajaran PAI: Analisis Tantangan dan Peluang - Dini Dini; Mulyawan Safwandy Nugraha (CV. Berkah Cakrawala Inspirasi, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in instilling national values through the paradigm of religious moderation at SMA Azzainiyyah Nagrog, Sukabumi. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings reveal that PAI teachers act as agents of change through three primary dimensions: as designers of contextual learning integrating national values into religious materials, as facilitators of critical dialogue to cultivate moderate reasoning, and as living models demonstrating the alignment between faith and patriotism. The success of this role is supported by a school culture that harmonizes religious and national symbols, along with the collective commitment of the school community. However, challenges such as student background diversity, social media influence, an requires a systematic ecosystem of support, encompassing teacher competency enhancement, visionary school leadership, and parental partnership.